1988
DOI: 10.1111/j.1464-410x.1988.tb04294.x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Treatment of Adult Nocturia with Bumetanide

Abstract: The efficacy of 1 mg bumetanide on nocturia was compared with placebo in a randomised double-blind cross-over study in general practice. Twenty-eight patients, 13 females and 15 males, completed two treatment periods of 2 weeks' duration. During the placebo period the weekly number of nocturia episodes was 13.8 and during bumetanide treatment the number was reduced by 3.8. Ten males had a history of prostatic hypertrophy and in these patients treatment with bumetanide was not beneficial. In the remaining 18 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 5 publications
0
27
0
Order By: Relevance
“…27 A decrease of 4 nightly voids per week was seen in the treatment group only after excluding the 10 patients with benign prostatic hyperplasia (LOE 3).…”
Section: Conservative Managementmentioning
confidence: 90%
“…27 A decrease of 4 nightly voids per week was seen in the treatment group only after excluding the 10 patients with benign prostatic hyperplasia (LOE 3).…”
Section: Conservative Managementmentioning
confidence: 90%
“…However, the association between NP and HT has only been confirmed in 2017 by Yokoyama et al Some older and smaller studies support this association too: in 1996, Matthiesen et al, showed that mean arterial pressure is higher in patients with NP than in controls and higher night/day ratios of urinary sodium excretion are associated with raised blood pressure. Interestingly, two randomized controlled trials from 1988 showed that nocturia in elderly patients with NP is alleviated by giving loop diuretics during the day …”
Section: Nocturia Cardiac and Renal Functions: Improve Carementioning
confidence: 99%
“…Depending on the diagnosis and underlying cause(s), treatment options for nocturnal polyuria may include restriction of fluids in the evening, time release diuretics,19 afternoon naps, elevation of the legs, compression stockings, and treatment with antidiuretic hormone. Accumulation of fluid in the lower extremities in some patients may eliminate simple fluid restriction as an effective alternative.…”
Section: Treatment Optionsmentioning
confidence: 99%